2007
DOI: 10.1021/cb600429k
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Grafting to Endow Cell Permeability

Abstract: We report on a means to endow proteins with the ability to permeate mammalian cells without appending an exogenous domain. Our approach is to install a cationic patch on the surface of a target protein by the grafting of arginine residues. Doing so with GFP did not compromise conformational stability but enabled efficient cellular uptake that was dependent on cell-surface glycosaminoglycans. We anticipate that this cell-permeable variant of GFP, which obviates the need for transfection, will be useful for nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 31 publications
0
71
0
2
Order By: Relevance
“…When the replacement residues are all positively or all negatively charged, the resulting ''supercharged'' proteins can retain their activity while gaining unusual properties such as robust resistance to aggregation and the ability to bind oppositely charged macromolecules. For example, we reported that a green fluorescent protein with a ϩ36 net theoretical charge (ϩ36 GFP) was highly aggregation-resistant, could retain fluorescence even after being boiled and cooled, and reversibly complexed DNA and RNA through electrostatic interactions.A variety of cationic peptides and proteins have been observed to penetrate mammalian cells (18)(19)(20)(21)(22)(23)(24). We hypothesized that superpositively charged proteins such as ϩ36 GFP might also associate with negatively charged components of the cell membrane in a manner that results in cell penetration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the replacement residues are all positively or all negatively charged, the resulting ''supercharged'' proteins can retain their activity while gaining unusual properties such as robust resistance to aggregation and the ability to bind oppositely charged macromolecules. For example, we reported that a green fluorescent protein with a ϩ36 net theoretical charge (ϩ36 GFP) was highly aggregation-resistant, could retain fluorescence even after being boiled and cooled, and reversibly complexed DNA and RNA through electrostatic interactions.A variety of cationic peptides and proteins have been observed to penetrate mammalian cells (18)(19)(20)(21)(22)(23)(24). We hypothesized that superpositively charged proteins such as ϩ36 GFP might also associate with negatively charged components of the cell membrane in a manner that results in cell penetration.…”
mentioning
confidence: 99%
“…A variety of cationic peptides and proteins have been observed to penetrate mammalian cells (18)(19)(20)(21)(22)(23)(24). We hypothesized that superpositively charged proteins such as ϩ36 GFP might also associate with negatively charged components of the cell membrane in a manner that results in cell penetration.…”
mentioning
confidence: 99%
“…Supercharged proteins are a class of engineered proteins that can be fused with the target proteins for superior membrane penetration properties [35], providing an alternative to CPP 'tags' [11]. Liu and colleagues [36] have recently demonstrated a potent delivery vehicle for proteins using supercharged GFP (+36 GFP).…”
Section: Supercharged Proteinsmentioning
confidence: 99%
“…The basic mechanisms and applications of cationic CPPs have been widely studied [8][9][10][11][12]. Recent studies have reported the preparation of superpositively charged variants of green fluorescent protein (GFP) by mutating acidic amino acid residues (Glu and Asp) on the solvent-exposed surface to cationic amino acids residues (Arg and Lys), without a loss of proper folding [13][14][15][16]. Although wild-type GFP cannot permeate cells, superpositively charged GFPs can pass through cell membranes because of their highly positive two-dimensional cationic cluster on the solvent-exposed protein surface.…”
Section: Introductionmentioning
confidence: 99%